Release of fibrous microplastics from functional polyester garments through household washing - Klinkhammer, Kristina; Kolbe, Sabrina; Brandt, Stefan; Meyer, Jens; Ratovo, Karin; Bendt, Ellen; Rabe, Maike (Frontiers in Environmental Science, 2024)
The global increase of the amount of microplastics in aquatic systems is an ever-growing problem. Household laundering of synthetic textiles has been identified as one significant reason for the release of fibrous microplastics (FMP), although a high proportion of the waste water generated by the washing process is filtered by wastewater treatment plants, e.g. in Germany, before it enters the environment. The washing of garments made of synthetic materials is considered particularly critical. However, this study utilizing different functional polyester garments showed that mechanical raised textiles (e.g. fleece) do not generally have higher emission values than non-raised textiles, such as sports shirts and sports pants. During the washing process, the release of FMP can be influenced by different washing parameters, always aiming for a good washing result. The experiments showed, that the release of FMP into the aquatic environment can be reduced by the washing habits -especially a high washing machine load and a shortened washing time were found to be effective. type of raising rollers and coverings used, the ratio of pile and counter-pile, the number of raising rollers in the drum, the number of process steps and on factors such as process speed and contact pressure. This leads to various types of fabric surfaces. Besides that, household laundry is one of the major entry paths for FMPs into the environment (